Study of Settlement Pattern of Dungarpur District of Rajasthan - Binda, Varun; Chharang, Santosh (Advances in Social Sciences Research Journal, 2021)
The settlement indicates the spatial pattern of the human's functional activities at the local level, including residence, street structure, community areas, etc. Settlements represent one of the most dominant features made by men on the earth in the process of habitation. In the genetic term, settlements are the almost permanent abode of an organism. They represent "An organized colony of human beings together with the buildings, paths, and streets over which they travel." The settlement pattern is also an essential aspect of settlement geography for research. Within a particular region, different types of settlement patterns were found. The settlement pattern is controlled by various socio-economic, climatic, and different factors. In this research, the authors attempt to highlight the various settlements' patterns, sizes, and responsible factors.